ChemInform Abstract: Synthesis of Highly Functionalized Pyrrolidines as Tunable Templates for the Direct Access to (.+‐.)‐Coerulescine and the Tricyclic Core of Martinellines. Issue 31 (11th July 2013) - Le Goff, Ronan; Lawson, Ata Martin; Daich, Adam; Comesse, Sebastien
Abstract A series of tetrasubstituted pyrrolidines is synthesized by an aza‐Michael induced ring‐closure tandem reaction of bromide (II) with Michael acceptors (I), (IV), and (VI).